2023
DOI: 10.3390/educsci13070644
|View full text |Cite
|
Sign up to set email alerts
|

Student Adaptation, Loneliness and Mental Health Profiles during the Second Wave of the Pandemic COVID-19

Abstract: Since the COVID-19 pandemic, adolescent mental health difficulties have increased. To understand adolescent adjustment, it is important to explore both mental health difficulties and indicators of resilience and well-being. The primary aim of this study was to explore the associations among resilience, subjective well-being (SWB), fear of COVID-19, and loneliness among adolescents during the second wave of the pandemic. Additionally, the study aimed to identify student profiles based on these variables. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Several reviews, e.g., [25][26][27], examining the longitudinal changes in adolescent depression and anxiety symptoms before and during the COVID-19 pandemic indicated that mental health problems increased during the pandemic. To explore the pandemic's effects on Greek school communities, Lampropoulou et al [28], aiming to identify students' mental health profiles, revealed that more than half of the high-school students who participated in their study struggled to some degree during the second wave of the pandemic. Similarly, a sample of 8079 adolescents (aged 12-18 years) in China reported an increased prevalence of anxiety and depression levels associated with the pandemic [29].…”
Section: Impact Of the Covid-19 Pandemic On Resilience Outcomesmentioning
confidence: 99%
“…Several reviews, e.g., [25][26][27], examining the longitudinal changes in adolescent depression and anxiety symptoms before and during the COVID-19 pandemic indicated that mental health problems increased during the pandemic. To explore the pandemic's effects on Greek school communities, Lampropoulou et al [28], aiming to identify students' mental health profiles, revealed that more than half of the high-school students who participated in their study struggled to some degree during the second wave of the pandemic. Similarly, a sample of 8079 adolescents (aged 12-18 years) in China reported an increased prevalence of anxiety and depression levels associated with the pandemic [29].…”
Section: Impact Of the Covid-19 Pandemic On Resilience Outcomesmentioning
confidence: 99%